Association of saliva 25(OH)D concentration with body composition and proportion among pre‐pubertal and pubertal Polish children. Issue 5 (5th February 2020) - Pruszkowska‐Przybylska, Paulina; Sitek, Aneta; Rosset, Iwona; Sobalska‐Kwapis, Marta; Słomka, Marcin; Strapagiel, Dominik; Żądzińska, Elżbieta; Morling, Niels
Abstract: Objectives: Due to increasing problems with obesity and vitamin D deficiency among children, studies that tackle both problems together are needed. Methods: Data were collected from 182 randomly selected children aged 6‐13 years in primary schools in central Poland. Measures included anthropometric dimensions, body composition, questionnaires completed by participants' parents, and saliva samples. The level of 25(OH)D was assessed from the saliva samples using an enzyme‐linked immunosorbent assay kit. The children were divided into two groups: pre‐pubertal (girls below 10 years and boys below 11 years) and pubertal individuals (girls above 10 years and boys above 11 years). Results: The 25(OH)D concentrations were higher in late spring (June) among pre‐pubertal children than in the autumn (November‐December) among pubertal children. The level of 25(OH)D was positively correlated with body cell mass (BCM, %) among all children (pubertal: R = 0.20, P = .044; pre‐pubertal: R = 0.23, P = .041) and inversely associated with waist‐to‐hip ratio (WHR) among pubertal children of both sexes ( R = ‑0.25; P = .031). The stepwise regression analysis revealed that investigation in spring (June) and breastfeeding was associated with increased muscle mass (MM, %) (beta = 0.253, P = .003 and beta = 0.225, P = .005, respectively) and total body water (TBW, %) (beta = 0.276, P = .004 and beta = 0.246, P = .011, respectively) and was associated with decreased body mass index (BMI; beta = −0.222, P = .024 and beta = −0.269, P = .009, respectively) and fat mass (%) (beta = −0.288, P = .003 and beta = −0.266, P = .005, respectively). Conclusions: Season of salivary sampling and breastfeeding status were more strongly associated with body components, BMI and WHR, than 25(OH)D concentrations.